A (2+1)-dimensional time-dependent Date–Jimbo–Kashiwara–Miwa equation: Painlevé integrability and multiple soliton solutions. (15th February 2020) - Wazwaz, Abdul-Majid
Abstract: In this work, we extend the (2+1)-dimensional Date- Date–Jimbo–Kashiwara–Miwa equation to a new version with time-dependent coefficients. The integrability property of this developed equation is demonstrated by exhibiting the Painlevé test. We show that this time-dependent equation admits multiple real and multiple complex soliton solutions. Moreover, we derive other solitonic and periodic solutions.